HUBUNGAN BRAND IMAGE DENGAN KEPUTUSAN PENGGUNAAN LAYANAN DI INSTALASI RAWAT JALAN RSIA SITTI KHADIJAH 1 MAKASSAR - Sriyani Windarti (POLITEKNIK PIKSI GANESHA, 2022)
Brand image is a perception or view of a brand, the perception can be good or bad. Brand image consists of components of hospital identity, physical environment, contact personnel, service offering, and hospital individuality. This study aims to determine the relationship between brand image and decisions to use health services at the Outpatient Installation of RSIA Sitti Khadijah 1 Makassar. The type of research used is quantitative research with a designcross sectional study.The sampling technique is purposive sampling with a total of 99 respondents. Hypothesis testing used is chi square test analysis. The results showed that the significant value of hospital identity (p=0.006), physical environment (p=0.000), contact personnel (p=0.017), service offering (p=0.006), hospital individuality (p=0.006). The results of this study indicate that there is a significant relationship between all independent variables, namely hospital identity, physical environment, contact personnel, service offerings, hospital individuality and the decision to use health services. This research can be a reference for hospitals to improve services in order to retain customers and increase the number of visits to hospitals. Keywords: Brand image, patient decision, hospital, health services.